2008
DOI: 10.1124/dmd.108.021154
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of the Carcinogen-Metabolizing Enzyme Cytochrome P450 1a1 by Vanadium

Abstract: ABSTRACT:Vanadium (V 5؉ ), a heavy metal contaminant with important toxicological consequences, has received considerable attention as an anticancer agent, although the mechanisms remain unknown. As a first step to investigate these mechanisms, we examined the effect of V 5؉ (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As such, we have previously demonstrated that V 5+ was able to decrease the TCDD-mediated induction of Cyp1a1 at mRNA, protein, and catalytic activity levels in the mouse hepatoma, Hepa 1c1c7 cells (Anwar-Mohamed and El-Kadi 2008). Therefore, the objectives of the current study were to examine the effect of coexposure to V 5+ and TCDD on the expression of human CYP1A1 using human hepatoma HepG2 cells and to investigate the underlying mechanisms involved in this modulation.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…As such, we have previously demonstrated that V 5+ was able to decrease the TCDD-mediated induction of Cyp1a1 at mRNA, protein, and catalytic activity levels in the mouse hepatoma, Hepa 1c1c7 cells (Anwar-Mohamed and El-Kadi 2008). Therefore, the objectives of the current study were to examine the effect of coexposure to V 5+ and TCDD on the expression of human CYP1A1 using human hepatoma HepG2 cells and to investigate the underlying mechanisms involved in this modulation.…”
mentioning
confidence: 93%
“…To date, very little information is available on the effect of V 5+ on the CYP1A1 expression and function (Anwar-Mohamed and El-Kadi 2008). As such, we have previously demonstrated that V 5+ was able to decrease the TCDD-mediated induction of Cyp1a1 at mRNA, protein, and catalytic activity levels in the mouse hepatoma, Hepa 1c1c7 cells (Anwar-Mohamed and El-Kadi 2008).…”
mentioning
confidence: 98%
“…Vanadium complexes show a variety of biological properties, and oxidovanadium(IV) complexes have been used to prevent and improve dexamethasone‐induced insulin resistance in 3T3‐L1 adipocytes 21. These compounds have also been used in receptor‐mediated signals22 and as anticancer agents 23,24. Recently, we have reported the antiamoebic activity of various vanadium complexes, which gave encouraging results in in vitro experiments 25,26…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from our laboratory demonstrated that V 5+ was able to decrease the TCDD‐mediated induction of Cyp1a1 and Nqo1 at mRNA, protein, and catalytic activity levels in the mouse hepatoma Hepa 1c1c7 cells (Anwar‐Mohamed and El‐Kadi, ; Anwar‐Mohamed and El‐Kadi, ) and in human hepatoma HepG2 cells (Abdelhamid et al ., , ). However, it was not reported previously if V 5+ could affect TCDD‐mediated induction of Cyp1a1, Cyp1a2 and Cyp1b1 mRNA, protein or catalytic activity levels in the kidney, lung or heart of C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, few studies have examined the combined toxicological effects of these ligands with heavy metals such as V 5+ . At the in vitro level, we recently reported that V 5+ was able to decrease the TCDD‐mediated induction of Cyp1a1 and Nqo1 at mRNA, protein and catalytic activity levels in the mouse hepatoma Hepa 1c1c7 cells, which were derived from BW7756 mouse hepatoma that arose in a C57BL/6 mouse (Anwar‐Mohamed and El‐Kadi, , ) and in human hepatoma HepG2 cells, which were derived from the liver tissue of a 15‐year‐old Caucasian American male with a well‐differentiated hepatocellular carcinoma (Abdelhamid et al ., , ). However, to the best of our knowledge, there has been no previous attempt to examine the effect of V 5+ on the regulation of AhR‐regulated genes in the presence and absence of TCDD in extrahepatic tissues in vivo .…”
Section: Introductionmentioning
confidence: 99%